Exile and Execution in Medieval and Early Modern Society - Aloni, Gila,; Tracy, Larissa, (Explorations in Medieval Culture ;, 2026)
In both exile and execution, society must be complicit; people must be willing to ostracize their neighbors or watch their execution, participating in the spectacle that reifies the power of the state. This collection investigates the relationship between the exiled and the landscape, physical or psychological, into which they are (dis)placed in conversation with accounts of execution, constructed by the authorities or invented to criticize the whole system. The essays cover a broad range of material including early Irish penitential literature, French courtly epics, English legendary histories, Spanish textual evidence of executions, and legal treatises governing both exile and execution in the late Middle Ages and early modern period. Contributors are Gillian Adler, Gila Aloni, Kim Bergqvist, Karen Casey Casebier, Westley Follet, Radosław Kotecki, Mireille J. Pardon, Ben Parsons, Bojana Radovanović, Abel de Lorenzo Rodríguez, Susan Small, and Larissa Tracy.